Strategi Pengembangan Program One Village One Product (OVOP) di Kelurahan Wonorejo Kecamatan Marpoyan Damai Kota Pekanbaru - Hamdani Hamdani; Anuar Rasyid; Hasim As’Ari; Zulkarnain Zulkarnain (SYNERGY: Jurnal Bisnis dan Manajemen, 2026)
One Village One Product (OVOP) is a regional development approach to produce globally competitive products while maintaining local characteristics. Wonorejo Sub-district has 162 UMKM with potential for OVOP development, yet faces challenges in capital access, marketing, and product standardization. This was study aimed to analyze the existing conditions and formulate development strategies for the OVOP program in Wonorejo Sub-district.  This qualitative research used survey methods with purposive sampling, collecting data through in-depth interviews, observation, and FGD. Data analysis employed Miles and Huberman's interactive model and SWOT analysis. The existing condition shows that Wonorejo has significant local economic potential in the culinary sector, but lacks a distinctive product identity as a regional icon. SWOT analysis identified four strategic directions: (S-O) optimizing UMKM through government training and expanding digital marketing; (W-O) improving packaging quality and establishing a signature product; (S-T) maintaining customer trust and developing product innovation; (W-T) promoting business legality and diversifying raw material sources. Wonorejo Sub-district has great potential for OVOP development through institutional strengthening, human resource capacity building, and cross-sector collaboration involving government, academia, and private sectors